5.20.7 Problems 601 to 700

Table 5.919: Second or higher order ODE with constant coefficients

#

ODE

Mathematica

Maple

2391

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

2392

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

2402

\[ {}y^{\prime \prime }+y = \sec \left (t \right ) \]

2403

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = t \,{\mathrm e}^{2 t} \]

2404

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = \left (t^{2}+1\right ) {\mathrm e}^{t} \]

2405

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = t \,{\mathrm e}^{3 t}+1 \]

2406

\[ {}3 y^{\prime \prime }+4 y^{\prime }+y = \sin \left (t \right ) {\mathrm e}^{-t} \]

2407

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = t^{{5}/{2}} {\mathrm e}^{-2 t} \]

2408

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sqrt {t +1} \]

2409

\[ {}y^{\prime \prime }-y = f \left (t \right ) \]

2412

\[ {}m y^{\prime \prime }+c y^{\prime }+k y = F_{0} \cos \left (\omega t \right ) \]

2545

\[ {}y^{\prime \prime }-y = 0 \]

2546

\[ {}6 y^{\prime \prime }-7 y^{\prime }+y = 0 \]

2547

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

2548

\[ {}3 y^{\prime \prime }+6 y^{\prime }+2 y = 0 \]

2549

\[ {}y^{\prime \prime }-3 y^{\prime }-4 y = 0 \]

2550

\[ {}2 y^{\prime \prime }+y^{\prime }-10 y = 0 \]

2551

\[ {}5 y^{\prime \prime }+5 y^{\prime }-y = 0 \]

2552

\[ {}y^{\prime \prime }-6 y^{\prime }+y = 0 \]

2553

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

2556

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

2557

\[ {}2 y^{\prime \prime }+3 y^{\prime }+4 y = 0 \]

2558

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

2559

\[ {}4 y^{\prime \prime }-y^{\prime }+y = 0 \]

2560

\[ {}y^{\prime \prime }+y^{\prime }+2 y = 0 \]

2561

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

2562

\[ {}2 y^{\prime \prime }-y^{\prime }+3 y = 0 \]

2563

\[ {}3 y^{\prime \prime }-2 y^{\prime }+4 y = 0 \]

2564

\[ {}y^{\prime \prime }+w^{2} y = 0 \]

2567

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

2568

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

2569

\[ {}9 y^{\prime \prime }+6 y^{\prime }+y = 0 \]

2570

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

2571

\[ {}6 y^{\prime \prime }+2 y^{\prime }+y = 0 \]

2572

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

2583

\[ {}y^{\prime \prime }+y = \sec \left (t \right ) \]

2584

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = t \,{\mathrm e}^{2 t} \]

2585

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = \left (t^{2}+1\right ) {\mathrm e}^{t} \]

2586

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = t \,{\mathrm e}^{3 t}+1 \]

2587

\[ {}3 y^{\prime \prime }+4 y^{\prime }+y = \sin \left (t \right ) {\mathrm e}^{-t} \]

2588

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = t^{{5}/{2}} {\mathrm e}^{-2 t} \]

2589

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sqrt {t +1} \]

2590

\[ {}y^{\prime \prime }-y = f \left (t \right ) \]

2594

\[ {}y^{\prime \prime }+3 y = t^{3}-1 \]

2595

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = t \,{\mathrm e}^{\alpha t} \]

2596

\[ {}y^{\prime \prime }-y = t^{2} {\mathrm e}^{t} \]

2597

\[ {}y^{\prime \prime }+y^{\prime }+y = t^{2}+t +1 \]

2598

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-t} \]

2599

\[ {}y^{\prime \prime }+5 y^{\prime }+4 y = t^{2} {\mathrm e}^{7 t} \]

2600

\[ {}y^{\prime \prime }+4 y = t \sin \left (2 t \right ) \]

2601

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = \left (3 t^{7}-5 t^{4}\right ) {\mathrm e}^{3 t} \]

2602

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 2 \cos \left (t \right )^{2} \]

2603

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 2 \cos \left (t \right )^{2} {\mathrm e}^{t} \]

2604

\[ {}y^{\prime \prime }+y^{\prime }-6 y = \sin \left (t \right )+t \,{\mathrm e}^{2 t} \]

2605

\[ {}y^{\prime \prime }+y^{\prime }+4 y = t^{2}+\left (2 t +3\right ) \left (1+\cos \left (t \right )\right ) \]

2606

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{t}+{\mathrm e}^{2 t} \]

2607

\[ {}y^{\prime \prime }+2 y^{\prime } = 1+t^{2}+{\mathrm e}^{-2 t} \]

2608

\[ {}y^{\prime \prime }+y = \cos \left (t \right ) \cos \left (2 t \right ) \]

2609

\[ {}y^{\prime \prime }+y = \cos \left (t \right ) \cos \left (2 t \right ) \cos \left (3 t \right ) \]

2610

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = t^{{3}/{2}} {\mathrm e}^{3 t} \]

2671

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = {\mathrm e}^{2 t} \]

2672

\[ {}2 y^{\prime \prime }+y^{\prime }-y = {\mathrm e}^{3 t} \]

2673

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-t} \]

2674

\[ {}y^{\prime \prime }+y = t^{2} \sin \left (t \right ) \]

2675

\[ {}y^{\prime \prime }+3 y^{\prime }+7 y = \cos \left (t \right ) \]

2676

\[ {}y^{\prime \prime }+y^{\prime }+y = t^{3} \]

2677

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = {\mathrm e}^{4 t} \]

2678

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{-t} \]

2679

\[ {}y^{\prime \prime }+y = \sin \left (t \right ) \]

2680

\[ {}y^{\prime \prime }+y = t \sin \left (t \right ) \]

2681

\[ {}y^{\prime \prime }-2 y^{\prime }+y = t \,{\mathrm e}^{t} \]

2682

\[ {}y^{\prime \prime }-2 y^{\prime }+7 y = \sin \left (t \right ) \]

2683

\[ {}y^{\prime \prime }+y^{\prime }+y = 1+{\mathrm e}^{-t} \]

2684

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} 2 & 0\le t \le 3 \\ 3 t -7 & 3<t \end {array}\right . \]

2685

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 \left (t -3\right ) \operatorname {Heaviside}\left (t -3\right ) \]

2686

\[ {}y^{\prime \prime }+y^{\prime }+y = \operatorname {Heaviside}\left (t -\pi \right )-\operatorname {Heaviside}\left (t -2 \pi \right ) \]

2687

\[ {}y^{\prime \prime }+4 y = \left \{\begin {array}{cc} 1 & 0\le t <4 \\ 0 & 4<t \end {array}\right . \]

2688

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} \sin \left (t \right ) & 0\le t <\pi \\ \cos \left (t \right ) & \pi \le t \end {array}\right . \]

2689

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} \cos \left (t \right ) & 0\le t <\frac {\pi }{2} \\ 0 & \frac {\pi }{2}\le t \end {array}\right . \]

2690

\[ {}y^{\prime \prime }+2 y^{\prime }+y = \left \{\begin {array}{cc} \sin \left (2 t \right ) & 0\le t <\frac {\pi }{2} \\ 0 & \frac {\pi }{2}\le t \end {array}\right . \]

2691

\[ {}y^{\prime \prime }+y^{\prime }+7 y = \left \{\begin {array}{cc} t & 0\le t <2 \\ 0 & 2\le t \end {array}\right . \]

2692

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} t^{2} & 0\le t <1 \\ 0 & 1\le t \end {array}\right . \]

2693

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \left \{\begin {array}{cc} 0 & 0\le t <1 \\ t & 1\le t <2 \\ 0 & 2\le t \end {array}\right . \]

2694

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = \delta \left (t -1\right ) \]

2695

\[ {}y^{\prime \prime }+4 y = \sin \left (t \right )+\delta \left (t -\pi \right ) \]

2696

\[ {}y^{\prime \prime }+y^{\prime }+y = 2 \delta \left (t -1\right )-\delta \left (t -2\right ) \]

2697

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-t}+3 \delta \left (t -3\right ) \]

2710

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0 \]

2711

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+5 y^{\prime }+12 y = 0 \]

2712

\[ {}y^{\prime \prime \prime \prime }-5 y^{\prime \prime \prime }+6 y^{\prime \prime }+4 y^{\prime }-8 y = 0 \]

2713

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 0 \]

2714

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+14 y^{\prime \prime }-20 y^{\prime }+25 y = 0 \]

2715

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

2716

\[ {}y^{\left (5\right )}-2 y^{\prime \prime \prime \prime }+y^{\prime \prime \prime } = 0 \]

2717

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+y^{\prime \prime }+2 y^{\prime }-2 y = 0 \]

2718

\[ {}y^{\prime \prime \prime }+y^{\prime } = \tan \left (t \right ) \]

2719

\[ {}y^{\prime \prime \prime \prime }-y = g \left (t \right ) \]

2720

\[ {}y^{\prime \prime \prime \prime }+y = g \left (t \right ) \]

2721

\[ {}y^{\prime \prime \prime }+y^{\prime } = 2 t^{2}+4 \sin \left (t \right ) \]

2722

\[ {}y^{\prime \prime \prime }-4 y^{\prime } = t +\cos \left (t \right )+2 \,{\mathrm e}^{-2 t} \]